2018
DOI: 10.1111/ans.14895
|View full text |Cite
|
Sign up to set email alerts
|

Topical haemostatic powder as a novel endoscopic therapy for severe colonic diverticular bleeding

Abstract: Background: Although most diverticular bleeding resolve spontaneously, up to 30% can bleed torrentially, necessitating angioembolization, endoscopic or surgical intervention. Non-contact endoscopic therapies, such as topical haemostatic powders, do not require precise targeting and are attractive because identification of specific culprit diverticulum is difficult. While their use in non-variceal upper gastrointestinal bleeding is well established, its role in lower gastrointestinal bleeding remains unclear. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In a multicenter prospective study, the EndoClot polysaccharide hemostatic system (EndoClot Plus Inc., Santa Clara, California, USA) was used to treat diverticular bleeding; successful hemostasis was achieved in 83 % of the patients, while the remaining two cases (17 %) rebled secondary to malignancy and a cecal ischemic ulcer [105]. A systematic review by Chen et al [106] and two small studies [107,108] also described encouraging results for Hemospray (Cook Medical, Bloomington, Indiana, USA) in cases of actively bleeding LGIB lesions.…”
Section: Diverticular Bleedingmentioning
confidence: 99%
“…In a multicenter prospective study, the EndoClot polysaccharide hemostatic system (EndoClot Plus Inc., Santa Clara, California, USA) was used to treat diverticular bleeding; successful hemostasis was achieved in 83 % of the patients, while the remaining two cases (17 %) rebled secondary to malignancy and a cecal ischemic ulcer [105]. A systematic review by Chen et al [106] and two small studies [107,108] also described encouraging results for Hemospray (Cook Medical, Bloomington, Indiana, USA) in cases of actively bleeding LGIB lesions.…”
Section: Diverticular Bleedingmentioning
confidence: 99%
“…In the two other cases (gastric ulcerations with minor stigmata of recent hemorrhage), using Hemospray ® was not appropriate. Studies have described the use of Hemospray ® in various causes of lower GIB, with high rates of immediate hemostasis (10,23,24). Interesting results have been published in severe diverticular bleeding with immediate hemostasis in a series of ten patients, with no recurrence (24).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in ▶ Fig. 1, out of 974 studies initially identified, and after exclusion of papers not fulfilling the inclusion criteria, 9 potentially relevant studies [9][10][11][12][13][14][15][16][17] with 194 patients were included. The main characteristics of the included studies are reported in ▶ Table 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…All studies were Western series, except for a single small retrospective cohort from Singapore [13].…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation